2013
DOI: 10.1172/jci69091
|View full text |Cite
|
Sign up to set email alerts
|

Coagulation factor VA2440G causes east Texas bleeding disorder via TFPIα

Abstract: The autosomal dominantly inherited east Texas bleeding disorder is linked to an A2440G variant in exon 13 of the F5 gene. Affected individuals have normal levels of coagulation factor V (FV) activity, but demonstrate inhibition of global coagulation tests. We demonstrated that the A2440G mutation causes upregulation of an alternatively spliced F5 transcript that results in an in-frame deletion of 702 amino acids of the large activation fragment, the B domain. The approximately 250-kDa FV isoform (FV-short), wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
274
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 122 publications
(286 citation statements)
references
References 42 publications
9
274
1
Order By: Relevance
“…The recent elucidation of the molecular mechanisms of the East Texas Bleeding disorder revealed that FV‐Short, a splice variant of FV lacking 702 amino acid residues of the activation peptide B domain, is an important carrier of TFPIα in circulation 23. In this disease, a point mutation in the FV gene activates a normally existing but inefficient splice donor site in the codon for S756 and as a result affected individuals have greatly increased levels of circulating FV‐Short.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The recent elucidation of the molecular mechanisms of the East Texas Bleeding disorder revealed that FV‐Short, a splice variant of FV lacking 702 amino acid residues of the activation peptide B domain, is an important carrier of TFPIα in circulation 23. In this disease, a point mutation in the FV gene activates a normally existing but inefficient splice donor site in the codon for S756 and as a result affected individuals have greatly increased levels of circulating FV‐Short.…”
Section: Discussionmentioning
confidence: 99%
“…The FV‐Short binds TFPIα with high affinity and through mechanisms that are yet to be elucidated, the concentration of FV‐Short/TFPIα complexes in circulation are more than 10‐fold increased as compared to unaffected individuals. In individuals with the wild‐type allele, the concentration of the circulating FV‐Short is not yet elucidated but can be estimated to be in the sub‐nM range (≈0.1‐0.2 nmol L −1 ), approximately 100‐fold lower than the concentration of full length FV 23. We now demonstrate that FV‐Short not only is an important carrier for TFPIα in circulation but also functions as an efficient synergistic TFPIα cofactor together with protein S in the inhibition of FXa.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations